"Peer effects" in capital structure decision of Chinese firms-empirical investigation based on Chinese a-share listed firms. Issue 3 (6th August 2018) - Zhong, Tianli; Zhang, Tianyu
Abstract : Purpose: The purpose of this paper is to identify if peer firms' capital structure decision plays a role in determining focal firms' capital structure decision, despite the fact that correlated effects can also lead to co-movement of financing behavior among firms from the same industry (i.e. industry-specific capital structure). Design/methodology/approach: Instead of using relative measurement (of individual outcome variable over industry variable) as in previous work, this paper borrows the linear-in-means model and, after controlling for potential endogeneity problems, directly identifies the existence of peer effects with coefficient estimation. To deal with correlated effects, additional empirical investigations such as test of heterogeneity in direction and scale, social multiplier identification test and instrumental regression test based on another instrumental variable (that is less influenced by correlated effects) are performed. Findings: Using data from Chinese listed firms, this paper, for the first time, identifies the presence of peer effects in capital structure and debt maturity decision. Further investigations show that first, focal firms react asymmetrically to peer firms' debt adjustment of different direction and scale. Second, social multiplier, a unique attribute of peer effects, is identified in the leverage choices. Third, the significant correlation of capital structure decision remains even if we use another "correlated effects-immune" instrument. All these results point to the fact that peer effects, rather than correlated effects, play a significant role in determining capital structure. Practical implications: The empirical results of this paper provide strong evidence that firms, driven by motivations such as either learning or competition, will actively react to peers' financial decisions. As the bridge between individual firms and the industry, social multiplier can be fully taken advantage of to induce positive spillover of good management practices and prohibit inefficient decisions from spreading. Originality/value: This paper theoretically and empirically introduces peer effects – a well-acknowledged social concept – into capital structure decision of Chinese listed firms, thus both complementing the traditional capital structure theory and providing an empirical paradigm for peer effects research.